2021
DOI: 10.1177/00258172211018380
|View full text |Cite
|
Sign up to set email alerts
|

Witchcraft allegations and untouchability as forms of violence upon women in Nepal: A 7-year study

Abstract: The Nepalese constitution guarantees equal rights to both men and women regardless of caste, race, or ethnicity. However, the centuries-old superstitious practice of caste-based hierarchy in the Hindu community and discrimination against people of lower caste are still prevalent. Furthermore, witchcraft allegations are also not uncommon. Both these practices are derogatory and humiliating and violate human rights, and the law can penalise them in both instances. Due to the intersection of gender and caste, wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The result is slightly higher than this study which found that one-fifth of women experienced home bullying, and one-third reported experiencing domestic violence. This result is consistent with the assess that found that married women are bullying in different ways (Bradley et al, 2021;Nepal et al, 2021). The statistical analysis carried out in this study provides insight into a number of parameters related to the frequency of physical punishment among Nepali married women.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The result is slightly higher than this study which found that one-fifth of women experienced home bullying, and one-third reported experiencing domestic violence. This result is consistent with the assess that found that married women are bullying in different ways (Bradley et al, 2021;Nepal et al, 2021). The statistical analysis carried out in this study provides insight into a number of parameters related to the frequency of physical punishment among Nepali married women.…”
Section: Discussionsupporting
confidence: 91%
“…This study also revealed that sufferers of harassment were more than one more likely with the habit of taking tobacco smoking than the use of fermented malt. Furthermore the substantial connotations between harassment and psychological problems of married ladies left to corporal punishment (Chapin, 2016;Pandey et al, 2023;Nepal et al, 2021). However, home bullying and corporal punishment were not significantly linked but they are related to each other.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation